Orthodontic Management of a Severely Rotated Maxillary Central Incisor with a Modified Whip Appliance in Mixed Dentition Period - Sinaee, Neda; Mousavi, Mohammad; Nouri, Nadia (Journal of Dental School, 2019)
Objectives Tooth rotation is one of the most prevalent dental anomalies. Early management of rotated teeth would prevent possible occlusal interferences. The purpose of this case report was to introduce a fixed-removable appliance, which can efficiently correct severely rotated anterior teeth in a short duration of time in mixed dentition period. Case A 7-year-old boy with a Class I malocclusion was referred to the Orthodontics Department, School of Dentistry at Kerman University of Medical Sciences with the chief complaint of severe rotation of one of his maxillary central incisors. A whip appliance, which included a removable orthodontic appliance, a cantilever spring (whip) and a bonded tube, was used to treat this rotation. After 4 weeks, the upper right central incisor was aligned and overcorrected completely. A circumferential supracrestalfibrotomy was performed to prevent relapse. Conclusion In the present case, we treated a severely rotated central incisor in a short duration of timeusing the whip appliance. This appliance can be utilized effectively in emergency situations such as traumatic occlusion of central incisors